2012
DOI: 10.1007/s12192-011-0306-2
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative method for detection of spliced X-box binding protein-1 (XBP1) mRNA as a measure of endoplasmic reticulum (ER) stress

Abstract: Endoplasmic reticulum (ER) stress is increasingly recognized as an important mechanism in a wide range of diseases including cystic fibrosis, alpha-1 antitrypsin deficiency, Parkinson's and Alzheimer's disease. Therefore, there is an increased need for reliable and quantitative markers for detection of ER stress in human tissues and cells. Accumulation of unfolded or misfolded proteins in the endoplasmic reticulum can cause ER stress, which leads to the activation of the unfolded protein response (UPR). UPR si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 8 publications
3
114
0
Order By: Relevance
“…This hypothesis is supported by our data, which demonstrated PA and Tun activated UPR pathways with different kinetics. In the present study, we found that Tun-induced spliced XBP1 mRNA accumulation decreased within 12 h. However, the PA-induced the accumulation of spliced XBP1 mRNA sustained high levels more than 24 h. As the induction of spliced XBP1 mRNA is a potential biomarker of the degree of ER stress response [35,36], it is reasonable to suggest that PA-induced ER stress is persistent, but Tun-induced ER stress is transient. The difference of lasting time between PA and Tun-induced ER stress response might be a major reason for the different effects of PA and Tun-induced ER stress in apoptosis induction.…”
Section: Discussionsupporting
confidence: 45%
“…This hypothesis is supported by our data, which demonstrated PA and Tun activated UPR pathways with different kinetics. In the present study, we found that Tun-induced spliced XBP1 mRNA accumulation decreased within 12 h. However, the PA-induced the accumulation of spliced XBP1 mRNA sustained high levels more than 24 h. As the induction of spliced XBP1 mRNA is a potential biomarker of the degree of ER stress response [35,36], it is reasonable to suggest that PA-induced ER stress is persistent, but Tun-induced ER stress is transient. The difference of lasting time between PA and Tun-induced ER stress response might be a major reason for the different effects of PA and Tun-induced ER stress in apoptosis induction.…”
Section: Discussionsupporting
confidence: 45%
“…XBP1s qPCR-Splicing of XBP1 mRNA was measured by qPCR as described previously (31). Briefly, primers were designed to span the 26-base pair intron of XBP1 mRNA: forward, 5Ј-TGC TGA GTC CGC AGC AGG TG-3Ј; reverse, 5Ј-GCT GGC AGG CTC TGG GGA AG-3Ј).…”
Section: Methodsmentioning
confidence: 99%
“…136,[254][255][256] For instance, the phosphorylation state of EIF2A and/or of the major EIF2A kinases, including EIF2A kinase 1 (EIF2AK1, best known as HRI), 257 EIF2AK2 (best known as PKR), 258 and EIF2AK3 (best known as PERK), [259][260][261] can be assessed by immunoblotting, flow cytometry or immunofluorescence microscopy with phosphoneoepitope-specific antibodies. 260 The splicing status of X-box binding protein 1 (XBP1) mRNA, reflecting the activation of the ER stress sensor endoplasmic reticulum to nucleus signaling 1 (ERN1, best known as IRE1a), can be monitored by quantitative real-time RT-PCR, 262 as well as by flow cytometry or fluorescence microscopy, either in cells that express a fluorescently-tagged version of XBP1 263 or upon the administration of a self-quenched RNA probe that can be cleaved by IRE1a. 264 Finally, the nuclear redistribution of activating transcription factor 6 (ATF6) can be easily evaluated by fluorescence microscopy in cells that constitutively express GFP-or RFP-tagged variants of ATF6.…”
Section: E955691-6 Volume 3 Issue 9 Oncoimmunologymentioning
confidence: 99%